In Vitro Synergistic Activity of Combinations of Tetrahydroisoquinolines and Treatment Antibiotics against Multidrug-Resistant Salmonella - Rita Ayuk Ndip; Joelle Ngo Hanna; James Ajeck Mbah; Stephen Mbigha Ghogomu; Moses Njutain Ngemenya (Hindawi Limited, 2023)
The global burden of Salmonella infections remains high due to the emergence of multidrug resistance to all recommended treatment antibiotics. Tetrahydroisoquinolines (THIQs) have demonstrated promising activity against multidrug-resistant (MDR) Salmonella Typhi. Hence, their interaction with treatment antibiotics was investigated for possible synergy. Twenty combinations of five THIQs (1, 2, 3, 4, and 5) and four antibiotics were tested against each of 7 Salmonella isolates by the checkerboard method giving a total of 140 assays performed. Fractional inhibitory concentration indices (FICIs) were calculated, and isobolograms were plotted. In terms of FICI, synergism ranged from 0.078 to 0.5 and the highest magnitude (0.078) was recorded for chloramphenicol-THIQ 1 combination. In a total of 140 antibiotics-THIQs combination assays, 27 were synergistic (17%), 42 were additive (30%), 11 were antagonistic (7.8%), and 60 were indifferent (42%). The synergistic activity recorded for each antibiotic class in combination based on the total of 7 bacterial isolates tested ranged from 14.29% to 71.43%; the highest percentage was recorded for two combinations (chloramphenicol or sulphamethoxazole with THIQ 1). Ciprofloxacin-THIQ 1 combination showed additivity on all bacteria isolates tested (100%). Overall, THIQ 1 was the most synergistic and most additive in combination with three antibiotics (ampicillin, chloramphenicol, or sulphamethoxazole-trimethoprim). Some combinations of the THIQs and treatment antibiotics have shown high synergism which could potentially be efficacious against multidrug-resistant S. Typhi, hence this interaction should be further studied in vivo.